Elucidating the Pathogen Variability of Northern Leaf Blight of Maize (Zea mays L.) in Bihar, India - Md. Arshad Anwer; Amod Kumar; Md. Mahtab Rashid; Shamsher Ahmad; Md. Abu Nayyer; Mohammad Imran; Md. Reyaz Ahmad; Raj Narain Singh (Journal of Pure and Applied Microbiology)
Exserohilum turcicum is an emerging pathogen of maize causing the northern leaf blight (NLB) disease with severe losses. The disease prevails all over the area under production but has varying severity. A temperature of 13°C to 33°C, along with 75-84% relative humidity, favours the pathogen development and growth. Thus, the present investigation was carried out to assess the prevalence of the disease in Bihar and the cultural, morphological, and pathogenic variability among the population through extensive field surveys conducted in maize-growing areas of seven major maize-producing districts of Bihar, India. A total of twenty-one isolates were identified as E. turcicum, which showed varying colony characteristics, colony margin, margin colour, pigmentation, growth pattern, sporulation, conidial shape, conidial size, and conidial septa. However, all the isolates produced characteristic symptoms of cigar-shaped necrotic lesions with variation in disease reaction on the leaves of susceptible maize inbred line CM-202. The isolates were categorized into three phylogenetic clusters with a coefficient of 0.42 based on their variations. A similar trend was observed, and three clusters with a coefficient of 0.52 were confirmed based on the disease reaction under field conditions. The isolates constituting Cluster I were deemed high virulent, followed by Cluster II as moderate virulent, and Cluster III as low virulent. All the isolates were further identified as Setosphaeria turcica, a teleomorph stage of E. turcicum, through molecular identification using ITS sequence analysis. Conclusively, a higher variability among the pathogen population was present, thus leading to the disease emergence, and their virulence assessment will aid in the identification of races and simultaneously accelerate the resistance breeding programmes in maize.